Genome-wide analysis of genetic correlation in dementia with Lewy bodies, Alzheimer’s and Parkinson’s diseases - Guerreiro, Rita; Escott-Price, Valentina; Darwent, Lee; Parkkinen, Laura; Ansorge, Olaf; Hernandez, Dena; Nalls, Michael A.; Clark, Lorraine; Honig, Lawrence; Marder, Karen; Flier, Wiesje van der; Holstege, Henne; et al. (Elsevier, 2016)
The similarities between dementia with Lewy bodies (DLB) and both Parkinson's disease (PD) and Alzheimer's disease (AD) are many and range from clinical presentation, to neuropathological characteristics, to more recently identified, genetic determinants of risk. Because of these overlapping features, diagnosing DLB is challenging and has clinical implications since some therapeutic agents that are applicable in other diseases have adverse effects in DLB. Having shown that DLB shares some genetic risk with PD and AD, we have now quantified the amount of sharing through the application of genetic correlation estimates, and show that, from a purely genetic perspective, and excluding the strong association at the APOE locus, DLB is equally correlated to AD and PD.